The importance of a full 3D fluid dynamic analysis to evaluate the flow forces in a hydraulic directional proportional valve. Issue 5 (1st July 2014) - Amirante, Riccardo; Andrea Catalano, Luciano; Tamburrano, Paolo
Abstract : Purpose: – The purpose of this paper is to present a full 3D Computational Fluid Dynamics (CFD) analysis of the flow field through hydraulic directional proportional valves, in order to accurately predict the flow forces acting on the spool and to overcome the limitations of two-dimensional (2D) and simplified three-dimensional (3D) models. Design/methodology/approach: – A full 3D CAD representation is proposed as a general approach to reproduce the geometry of an existing valve in full detail; then, unstructured computational grids, which identify peculiar positions of the spool travel, are generated by means of the mesh generation tool Gambit. The computational grids are imported into the commercial CFD code Fluent, where the flow equations are solved assuming that the flow is steady and incompressible. To validate the proposed computational procedure, the predicted flow rates and flow forces are compared with the corresponding experimental data. Findings: – The superposition between numerical and experimental curves demonstrates that the proposed full 3D numerical analysis is more effective than the simplified 3D flow model that was previously proposed by the same authors. Practical implications: – The presented full 3D fluid dynamic analysis can be employed for the fluid-dynamic design optimization of the sliding spool and, more generally, of the internal profiles of the valve, with the objective of reducing the flow forces and thus the required control force. Originality/value: – The paper proposes a new computational strategy that is capable of recognizing all 3D geometrical details of a hydraulic directional proportional valve and that provides a significant improvement with respect to 2D and partially 3D approaches.